Zionism and the fin-de-siècle : cosmopolitanism and nationalism from Nordau to Jabotinsky - Stanislawski, Michael, 1952- (S. Mark Taper Foundation imprint in Jewish studies., 2001)
Michael Stanislawski's provocative study of Max Nordau, Ephraim Moses Lilien, and Vladimir Jabotinsky reconceives the intersection of the European fin de siecle and early Zionism. Stanislawski takes up the tantalizing question of why Zionism, at a particular stage in its development, became so attractive to certain cosmopolitan intellectuals and artists. With the help of hundreds of previously unavailable documents, published and unpublished, he reconstructs the ideological journeys of writer and critic Nordau, artist Lilien, and political icon Jabotinsky. He argues against the common conception of Nordau and Jabotinsky as nineteenth-century liberals, insisting that they must be understood against the backdrop of Social Darwinism in the West and the Positivism of Russian radicalism in the fin de siecle, as well as Symbolism, Decadence, and Art Nouveau. When these men turned to Zionism, Stanislawski says, far from abandoning their aesthetic and intellectual preconceptions, they molded Zionism according to their fin de siecle cosmopolitanism. Showing how cosmopolitanism turned to nationalism in the lives and work of these crucial early Zionists, this story is a fascinating chapter in European and Russian, as well as Jewish, cultural and political history. -- from publisher description.